2017
DOI: 10.2334/josnusd.16-0298
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nonsurgical periodontal therapy with oral hygiene instruction alone for chronic periodontitis

Abstract: We evaluated changes in clinical variablesand microbiological profiles of periodontopathogens among 56 patients with moderate to severe CP who were randomly assigned to oral hygiene instruction (OHI; n = 28) or nonsurgical periodontal treatment (NSPT; n = 28). Periodontal variables were assessed and subgingival plaque samples were obtained from deep pockets (≥5 mm) at baseline and 3 months after treatment. Real-time polymerase chain reaction was used to quantify Actinobacillus actinomycetemcomitans, Tannerella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
4
0
8
Order By: Relevance
“…Thus, the goal of periodontitis treatment is to prevent disease progression and to promote periodontal reconstruction by inhibiting plaque biofilm formation and the host immune response. The traditional treatment of periodontitis is mechanical plaque removal and drug treatment . Also, studies have confirmed a correlation between periodontitis and diabetes, and diabetic patients require long‐term hypoglycemic drugs or insulin to control blood glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the goal of periodontitis treatment is to prevent disease progression and to promote periodontal reconstruction by inhibiting plaque biofilm formation and the host immune response. The traditional treatment of periodontitis is mechanical plaque removal and drug treatment . Also, studies have confirmed a correlation between periodontitis and diabetes, and diabetic patients require long‐term hypoglycemic drugs or insulin to control blood glucose.…”
Section: Discussionmentioning
confidence: 99%
“…NSPT has been shown to provide improvement in clinical parameters namely, Visible Plaque Index (VPI), Gingival Bleeding Index (GBI), Probing Pocket Depth (PPD), Clinical Attachment Level (CAL), as well as reduction inflammation and in periodontal pathogens. NSPT was shown to induce a shift from a pre-dominant Gram negative to a Gram positive subgingival microbiota in the general population [2] and to significantly reduce total bacteria counts and positive sites of P. gingivalis and T. forsythia [3,4]. NSPT is also expected to reduce the serum resistin level, which otherwise is present in higher amount in case of periodontal inflammation with periodontitis patients as compared to healthy individuals [5].…”
Section: Introductionmentioning
confidence: 99%
“…Esses, variam de específicas ou não específicas. Há a hipótese da placa, e, mais recentemente, a "polimicrobiana sinergia e disbiose" 12,13 . A maioria destas teorias Identificam as bactérias como a principal causa de patogênese 13 .…”
Section: R E S U Lta D O Sunclassified